Influence of the Size and Shape of Halopyridines Guest Molecules G on the Crystal Structure and Conducting Properties of Molecular (Super)Conductors of (BEDT-TTF)4A+[M3+(C2O4)3]·G Family - Tatiana G. Prokhorova; Eduard B. Yagubskii; Andrey A. Bardin; Vladimir N. Zverev; Gennadiy V. Shilov; Lev I. Buravov (Magnetochemistry, 2021)
New organic (super)conductors of the β″-(BEDT-TTF)4A+[M3+(C2O4)3]G family, where BEDT-TTF is bis(ethylenedithio)tetrathiafulvalene; M is Fe; A is the monovalent cation NH4+; G is 2-fluoropyridine (2-FPy) (1); 2,3-difluoropyridine (2,3-DFPy) (2); 2-chloro-3-fluoropyridine (2-Cl-3-FPy) (3); 2,6-dichloropyridine (2,6-DClPy) (4); 2,6-difluoropyridine (2,6-DFPy) (5), have been prepared and their crystal structure and transport properties were studied. All crystals have a layered structure in which the conducting layers of BEDT-TTF radical cations alternate with paramagnetic supramolecular anionic layers {A+[Fe3+(C2O4)3]3−G0}2−. Crystals 1 undergo a structural phase transition from the monoclinic (C2/c) to the triclinic (P<semantics><mover accent="true">1¯</mover></semantics>) symmetry in the range 100–150 K, whereas crystals 2–5 have a monoclinic symmetry in the entire range of the X-ray experiment (100–300 K). The alternating current (ac) conductivity of salts 1–4 exhibits metallic behavior down to 1.4 K, whereas the salt 5 demonstrates the onset of a superconducting transition at 3.1 K. The structures and conducting properties of 1–5 are compared with those of the known monoclinic phases of the family containing different monohalopyridines as “guest” solvent molecules G.